2017
DOI: 10.1155/2017/8759764
|View full text |Cite
|
Sign up to set email alerts
|

Antigenotoxic Properties of Agaricus blazei against Hydrogen Peroxide in Human Peripheral Blood Cells

Abstract: The ability of Agaricus blazei mushroom in its dried and powdered mycelial form was evaluated for its antigenotoxic properties for the first time. Antigenotoxic effects in human peripheral blood cells against H2O2-induced DNA damage were examined in pretreatment and posttreatment protocol by comet assay. The results showed better antigenotoxic properties of Agaricus blazei on the interventional level, respectively, after treatment. Agaricus blazei in concentration of 250 μg/mL after treatment was most efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
2
9
0
2
Order By: Relevance
“…These results indicated that the protection of Grifola frondosa polysaccharides against age‐related brain impairment may be related to attenuation of oxidizing free radical–generated oxidative stress. Our results are similar to the previous works, which suggested that many favorable effects contributing in human health of mushrooms are based on their antioxidant properties .…”
Section: Discussionsupporting
confidence: 92%
“…These results indicated that the protection of Grifola frondosa polysaccharides against age‐related brain impairment may be related to attenuation of oxidizing free radical–generated oxidative stress. Our results are similar to the previous works, which suggested that many favorable effects contributing in human health of mushrooms are based on their antioxidant properties .…”
Section: Discussionsupporting
confidence: 92%
“…Many authors have reported that the increased antigenotoxic potential of isolated compounds may be because isolated phenolic compounds increase the cell's antioxidant capacity. Antioxidant capacity of compounds is associated with the following mechanism such as scavenging reactive oxygen species, donating hydrogen atoms or electrons, chelating metal cations, and enhancing the production of antioxidant enzymes and thus acting at a prevention level [5,18,24]. The beneficial effects of gallic acid have been attributed to their antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…Las diferencias de viabilidad (98,37 %) de los linfocitos de sangre periférica directamente expuestos a CQ registradas en el presente estudio en comparación con la viabilidad (50 %) de los linfocitos de sangre periférica en cultivo expuestas a la misma concentración de 5 µl (11) , así como, en las concentraciones de H 2 O 2 , en cultivo (100µM) (18) y directamente expuesto (734 mM) (12) utilizadas como control positivo; constituyen pruebas que el daño del ADN depende de la estructura y estado funcional de los linfocitos expuestos a CQ in vitro.…”
Section: Discussionunclassified